Report of Cotylophoron cotylophorum (Trematoda, Taramphistomidae) in bovine from Loreto, Perú - Sánchez, Nofre (2009)
The paramfistomosis is an infection caused by a trematode belonging to the sub order Paramphistomata, some their species are parasitics of the rumen and reticulo of ruminant. One of the most frequent trematodos in the world is Cotylophoron, it affects to domestic and wild ruminant, especially cows, sheep, goats and buffalos in tropical and subtropical regions. We evaluate the parasitism in 61 specimens of apparently healthy cattle (42 adult females and 19 under one year), fed with wild pastures on a farm located on the Nanay River Basin, Iquitos. The samples of fresh grounds were obtained by means of rectal palpation and processed by means of the method of Dennis modified. Two cows were sacrificed to collect mature parasites. The results indicate the presence of Cotylophoron cotylophorum (Fischoeder, 1901) Stiles & goldeberger, 1910, in the studied animals, which is a new record from Peru, being percentages of 62 and 53% respectively in adults and calves. The range of the parasitic load (egg/grams of grounds) in adults was 1—44 and 1—55 in animals smaller than one year. The study reveals the existence of the trematodo in a group of livestock crusader managed to the shepherding, although one ignores the negative effects that it could be causing in the reduced Amazon cattle raising.